2021
DOI: 10.3390/neurosci2010002
|View full text |Cite
|
Sign up to set email alerts
|

The Same Magnocellular Neurons Send Axon Collaterals to the Posterior Pituitary and Retina or to the Posterior Pituitary and Autonomic Preganglionic Centers of the Eye in Rats

Abstract: In rats, some parvocellular paraventricular neurons project to spinal autonomic centers. Using the virus tracing technique, we have demonstrated that some magnocellular paraventricular neurons, but not supraoptic neurons, also project to autonomic preganglionic centers of the mammary gland, gingiva, or lip. A part of these neurons has shown oxytocin immunoreactivity. In the present experiment, we have examined whether the same magnocellular neuron that sends fibers to the retina or autonomic preganglionic cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(50 reference statements)
0
3
0
1
Order By: Relevance
“…OT regulates visual activity at multiple levels. Histologically, the same magnocellular neurons can send axon collaterals to the posterior pituitary and retina or autonomic preganglionic centers of the eyes in rats ( Csáki et al, 2021 ). Under pathological conditions, intravitreal application of OT reduces diabetic retinopathy by significantly increasing outer nuclear layer thickness of the retina in streptozotocin-induced diabetic rats ( Degirmenci et al, 2019 ).…”
Section: Regulation Of Sensorimotor Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…OT regulates visual activity at multiple levels. Histologically, the same magnocellular neurons can send axon collaterals to the posterior pituitary and retina or autonomic preganglionic centers of the eyes in rats ( Csáki et al, 2021 ). Under pathological conditions, intravitreal application of OT reduces diabetic retinopathy by significantly increasing outer nuclear layer thickness of the retina in streptozotocin-induced diabetic rats ( Degirmenci et al, 2019 ).…”
Section: Regulation Of Sensorimotor Activitymentioning
confidence: 99%
“…Reduce diabetic retinopathy (Csáki et al, 2021;Degirmenci et al, 2019;Halbach et al, 2015;Marsh et al, 2021;York et al, 2017)…”
Section: Key Consideration Of Ot Clinical Trialsunclassified
“…A recent high-throughput single-cell RNA sequencing study suggests that some amacrine cells express neuropeptide genes, including Oxt [ 23 ]. However, oxytocin protein was not detected in mouse amacrine cells [ 20 ], so we infer that the retinal endogenous oxytocin may be from oxytocin neurons in the hypothalamus via blood circulation or direct projection [ 57 ]. The concentration of plasma oxytocin in adult mice is reported to be ~ 4 ng/ml [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin immunostaining revealed that some double-virus-labeled cells contain oxytocin as well. Figure 3 shows triple labeling in the SON and PVN of an adult 2-month-old rat [77].…”
Section: Usefulness Fluorescence Virus Tracers In the Study Of Neural...mentioning
confidence: 99%